BLENDED LEARNING: PROBLEMS AND SOLUTIONS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the concept of blended learning, which integrates traditional face-to-face instruction with online educational technologies. It highlights the main challenges associated with this approach, including unequal access to digital resources, low student motivation, insufficient time management skills, limited teacher readiness, and issues related to assessment and academic integrity. The study also proposes practical solutions such as improving digital infrastructure, enhancing student engagement through interactive methods, developing self-regulation skills, providing professional training for educators, and implementing reliable assessment strategies. The findings suggest that, despite its challenges, blended learning can significantly improve the quality and accessibility of education if effectively implemented.